La presse écrite: reflet de l'évolution de la famille québécoise de 1972 à 1995 - Fouquet, France (Université du Québec à Trois-Rivières, 2001)
Keywords: Devoir (Le); Famille

La représentation de la famille dans la peinture figurative nord-américaine durant la première moitié de la guerre froide (1945-1968) : les cas de Fairfield Porter, d'Alex Colville et de Jean Paul Lemieux - Scott, Christophe (Université du Québec à Montréal, 2021)
Keywords: Famille; Peinture

Parenté fluide: la quête des origines au Brésil et au Québec: dialogue entre parenté, droit et science - Allebrandt, Debora (Université de Montréal, 2013)
Keywords: Droit; Famille

Kin Keeping and Family Storytelling in Nineteenth-century French-Canadian Immigrant Letters: The Bergevin Corpus - Hurlburt, Sarah (Histoire sociale / Social History, 2017)
Number: 102
Keywords: Famille

Du théâtre en famille. Les Marchand et le théâtre de société - Robert, Lucie (Les Cahiers des Dix, 2019)
Number: 73
Keywords: Journalistes; Marchand-Dandurand; Joséphine; Théâtre

La construction du père québécois: le discours du mouvement familial et l’expérience des pères, 1945-1965 - Duhaime, Vincent (Université de Montréal, 2000)
Keywords: Famille

Pigs, Cows, Boarders, and...: Brothels, Taverns, and the Household Economy in Nineteenth-Century Montreal - Poutanen, Mary Anne (Labour / Le travail, 2014)
Keywords: Famille; Femmes

Working [on Imperial] Families: Bettina Bradbury's Imperial Re(turn) - Henderson, Jarrett (Labour / Le travail, 2014)
Keywords: Famille; Historiens

Une culture du voyage. Chronique d'une maisonnée d'Ahuntsic (1925-1945) - Campeau, André (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Number: 5
Keywords: Automobile; Famille

On ne naît pas mère, on le devient : le parcours de Julie Papineau - Smart, Patricia (De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime, 2014)
Keywords: Famille; Femmes; Mariage; Papineau (famille); Papineau; Louis-Joseph; Rébellions

Feminist Historians and Family History in Canada in the 1990's - Bradbury, Bettina (Journal of Family History, 2000)
Number: 3
Keywords: Famille; Féminisme; Histoire; Historiens

Collectionner les "monuments" du passé. La pratique antiquaire de Jacques Viger - Hamel, Nathalie (Revue d'histoire de l'Amérique française, 2005)
issued: 2005-22-00/2005-23-00
Keywords: Maires; Viger (famille); Viger; Jacques

Recovering Identities from the Judicial Archives of Quebec - Olson, Sherry; Poutanen, Mary Anne (Histoire sociale / Social History, 2024)
Keywords: Archives; Enfants; Famille; Femmes

Mary Travers Bolduc ou Madame Édouard Bolduc, pionnière de la chanson populaire au Québec - Melançon, Johanne (Les Cahiers de la Société québécoise de recherche en musique, 2021)
issued: 2021-21-00
Keywords: Bolduc; La; Chanson; Famille; Femmes

The Making and Unmaking of a University Museum: the McCord, 1921-1996 - Young, Brian J. (McGill-Queen's University Press, 2000)
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées

Location, Location, Location: David Ross McCord and the Makings of Canadian History - Harvey, Katryn (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2008)
Number: 1
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord; David Ross; Musée McCord; Musées

L’idéal maternel: discours, représentation et célébration des mères québécoises à l’occasion de la fête des mères, 1940-1980 - Marando, Nancy (Université de Montréal, 2006)
Keywords: Enfants; Famille; Femmes; Montreal Star; Presse (La)

Spirited Commitment: The Samuel and Saidye Bronfman Family Foundation, 1952-2007 - MacLeod, Roderick; Abrahamson, Eric John (McGill-Queen's University Press, 2010)
OCLC: ocn531018298
Keywords: Bronfman (famille); Bronfman; Samuel; Juifs; Philanthropie; Théâtre

Gustave Papineau (1829-1851), le dernier fils de Louis-Joseph - Aubin, Georges (Montréal en tête, 2012)
issued: 2012-22-00
Keywords: Avenir (L'); Journalistes; Papineau (famille); Papineau; Louis-Joseph

De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime - Smart, Patricia (Les Éditions du Boréal, 2014)
Keywords: Dessaulles; Henriette (Fadette); Famille; Femmes; Le Normand; Michelle; Marchand-Dandurand; Joséphine; Mariage; Papineau (famille); Rocbert de La Morandière; Élizabeth (Bégon; Élizabeth)

Jacques Viger: une biographie. Suivi des lettres de Jacques et Marguerite, 1808-1813 - Beaudoin, Léo; Blanchet, Renée (VLB Éditeur, 2009)
Keywords: Lacorne (famille); Maires; Milice; Société historique de Montréal; Viger; Jacques

Journaux de jeunes filles: vers un moi autonome - Smart, Patricia (De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime, 2014)
Keywords: Dessaulles; Henriette (Fadette); Famille; Femmes; Le Normand; Michelle; Mariage; Écrivains

"Te dire que je suis là": la correspondance d'Élisabeth Bégon - Smart, Patricia (De Marie de L'Incarnation à Nelly Arcan. Se dire, se faire par l’écriture intime, 2014)
Keywords: Famille; Michel de Villebois de La Rouvillière; Honoré; Rocbert de La Morandière; Élizabeth (Bégon; Élizabeth)

Searching for Intimacies beyond the Notman Photographs: The Case of Amy Redpath Roddick - Kirkland, Elizabeth; Poutanen, Mary Anne (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Enfants; Femmes; Golden Square Mile; Notman; William; Photographie; Redpath (famille)

La sociabilité montréalaise au XIXe siècle: la présence des cultures francophone et anglophone - Lamonde, Yvan (Histoire de Montréal et de sa région, 2012)
Keywords: Anglophones; Clubs; Expositions; Famille; Francophones; Imprimerie; Musique; Places publiques; Théâtre; Édition

Social Relations in Nineteenth-Century Montreal: Two Cultural Streams - Lamonde, Yvan (Montreal: The History of A North American City, 2018)
Keywords: Anglophones; Clubs; Expositions; Famille; Francophones; Imprimerie; Musique; Places publiques; Théâtre; Édition